Industrial training report University Malaysia Kelantan, Jeli Branch / Indera Syah Iyman Roslan - Roslan, Indera Syah Iyman (Perpustakaan Tengku Anis, 2017)
This special project was completed during the industrial training period from 5th February 2017 until 29 June 2017 in Faculty of Agro-Based Industry (FIAT) at University Malaysia Kelantan, Campus Jeli (UMKKJ). The trainee was placed under the library premise since there was no vacancy in the FIAT office under the supervision of Dr. Leony Tham Yew Seng which he is the Senior Lecturer of FIAT. The trainee has proposed a training workshop as his special project which is Build Your Own Website in 2 Hours. The training workshop focused on developing a website from free website development platform. In addition, the trainee was intended to promote FIAT expertise where the training workshop takes place as their stepping stone on selling their expertise in the industry. However, the trainee is also involved in other activities and programs which trainee was exposed to new experience and knowledge for the duration of industrial training. Throughout the industrial training, the trainee has gained the ability to communicate with confidence, multitasking and works on teamwork. The staff in UMKKJ is friendly and trainee they gave good cooperation with trainee during the industrial training period.